“The windy day isn’t the day for thatching”: An Irish Proverb and its Wider Links - Carson Williams, Fionnuala (Tautosakos darbai, 2026)
In line with Professor Kazys Grigas’s work on proverbs in Lithuania and their place in the overall European body, my article looks at one widespread proverb in Ireland: “Ní hé lá na gaoithe lá na scolb” (The windy day isn’t the thatching day) with a similar approach. Not only are there many examples of it in oral tradition in both Irish and English, but several variants within the island, one of which, the one quoted, mentions a regional kind of thatching. As well as variants and how their distribution ties in with the material culture, I look at parallels, such as “Ní hé lá na báistighe lá an phortaigh” (The rainy day isn’t the day for the bog), the bog already being a wet place. Occasionally, this short genre is attached to anecdotes about local people and other lore, which I also outline. Since thatched roofs themselves are now rare in Ireland, I will attempt to see what proverbs about procrastination have replaced this once common and widespread proverb.